Best dives Aruba, Bonaire & Curacao - Huber, Joyce (Hunter travel guides., 2009)
Based on Best Dives of the Caribbean, this book focuses on the ABC islands exclusively. Includes the latest and best dive and snorkel sites, each rated for visual excellence and marine life. The author's knowledge of the Caribbean sites is unparalleled. F